Dynamic sufficiency of the magnetically suspended train - Polyakov, V. A.; Khachapuridze, N. M. (Science and Transport Progress, 2013)
Purpose. The basic criterion of the magnetically suspended train's consumer estimation is a quality of its mechanical motion. This motion is realized in unpredictable conditions and, for purposefulness preservation, should adapt to them. Such adaptation is possible only within the limits of system’s dynamic sufficiency. Sufficiency is understood as presence at system of resources, which allow one to realize its demanded motions without violating actual restrictions. Therefore presence of such resources is a necessary condition of preservation of required purposefulness of train's dynamics, and verification of the mentioned sufficiency is the major component of this dynamic research. Methodology. Methods of the set theory are used in work. Desirable and actual approachability spaces of the train are found. The train is considered dynamically sufficient in zones of the specified spaces overlapping. Findings. Within the limits of the accepted treatment of train's dynamic sufficiency, verification of its presence, as well as a stock (or deficiency) of preservations can be executed by the search and the subsequent estimation of such overlapping zones. Operatively (directly during motion) it can be realized on the train's ODC with use, for example, of computer mathematics system Mathematica. It possesses extensive opportunities of highly efficient and, at the same time, demanding an expense concerning small resources information manipulation. The efficiency of using of created technique is illustrated on an example of vehicle's acceleration research. Calculation is executed with use of the constructed computer model of interaction of an independent traction electromagnetic subsystem of an artifact with its mechanical subsystem. Originality. The technique of verification of the high-speed magnetically suspended train's dynamic sufficiency is developed. The technique is highly efficient, it provides sufficient presentation and demands an expense of the moderate resources at use (especially in cases of not too high dimensions of spaces of conditions and decision-making of system). Practical value. The technique can be used with success during dynamic research, including the magnetically suspended trains.